A SINGLE-PHASE ACTIVE DEVICE FOR POWER QUALITY IMPROVEMENT OF LINEAR AND NON-LINEAR LOAD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A Transformer less Hybrid Series Active Filter THSeAF is gives to improve the power quality in single phase systems with critical loads. This paper helps the power quality issues related to Linear and Non-linear load. The control strategy is designed to prevent current harmonic distortions of non-linear loads to flow into the utility. While, protecting sensitive loads from voltage disturbances, sags, and swells initiated by the power system. This different forms hybrid topology allowing harmonic isolation and compensation of voltage distortions could absorb or inject the auxiliary power to the system.